ANALISIS SIKAP TOKOH UTAMA DALAM ROMAN ANAK â€œFREUNDSCHAFT FÃœR IMMER UND EWIG ?â€ KARYA TILDE MICHELS - LYANA, CYNTHIA (UNIVERSITAS NEGERI SURABAYA, 2016)
According to Thurstone, attitude was a form of feeling?s evaluation or reaction (Azwar, 2013: 5). In the Children?s novel, a character in the story shows the various attitudes that can be learning to the readers. The problem of this research: How is the attitude of the main characters in the children?s novel